Mendelian etiologies identified with whole exome sequencing in cerebral palsy. Issue 2 (24th January 2022) - Chopra, Maya; Gable, Dustin L.; Love‐Nichols, Jamie; Tsao, Alexa; Rockowitz, Shira; Sliz, Piotr; Barkoudah, Elizabeth; Bastianelli, Lucia; Coulter, David; Davidson, Emily; DeGusmao, Claudio; Fogelman, David; et al.
Abstract: Objectives: Cerebral palsy (CP) is the most common childhood motor disability, yet its link to single‐gene disorders is under‐characterized. To explore the genetic landscape of CP, we conducted whole exome sequencing (WES) in a cohort of patients with CP. Methods: We performed comprehensive phenotyping and WES on a prospective cohort of individuals with cryptogenic CP (who meet criteria for CP; have no risk factors), non‐cryptogenic CP (who meet criteria for CP; have at least one risk factor), and CP masqueraders (who could be diagnosed with CP, but have regression/progressive symptoms). We characterized motor phenotypes, ascertained medical comorbidities, and classified brain MRIs. We analyzed WES data using an institutional pipeline. Results: We included 50 probands in this analysis (20 females, 30 males). Twenty‐four had cryptogenic CP, 20 had non‐cryptogenic CP, five had CP masquerader classification, and one had unknown classification. Hypotonic‐ataxic subtype showed a difference in prevalence across the classification groups ( p  = 0.01). Twenty‐six percent of participants (13/50) had a pathogenic/likely pathogenic variant in 13 unique genes ( ECHS1, SATB2, ZMYM2, ADAT3, COL4A1, THOC2, SLC16A2, SPAST, POLR2A, GNAO1, PDHX, ACADM, ATL1 ), including one patient with two genetic disorders ( ACADM, PDHX ) and two patients with a SPAST ‐related disorder. The CP masquerader category had the highest diagnostic yield ( n  = 3/5, 60%), followed by the cryptogenic CP category ( n  = 7/24, 29%). Fifteen percent of patients with non‐cryptogenic CP ( n  = 3/20) had a Mendelian disorder on WES. Interpretation: WES demonstrated a significant prevalence of Mendelian disorders in individuals clinically diagnosed with CP, including in individuals with known CP risk factors.